Evidence for concerted ring opening and C-Br bond breaking in UV-excited bromocyclopropane. - Pandit, S; Preston, T; King, S; Vallance, C; Orr-Ewing, A (American Institute of Physics, 2016)
Photodissociation of gaseous bromocyclopropane via its A-band continuum has been studied at excitation wavelengths ranging from 230 nm to 267 nm. Velocity-map images of ground-state bromine atoms (Br), spin-orbit excited bromine atoms (Br*) and C3H5 hydrocarbon radicals reveal the kinetic energies of these various photofragments. Both Br and Br* atoms are predominantly generated via repulsive excited electronic states in a prompt photodissociation process in which the hydrocarbon co-fragment is a cyclopropyl radical. However, the images obtained at the mass of the hydrocarbon radical fragment identify a channel with total kinetic energy greater than that deduced from the Br and Br* images, and with a kinetic energy distribution that exceeds the energetic limit for Br + cyclopropyl radical products. The velocity-map images of these C3H5 fragments have lower angular anisotropies than measured for Br and Br*, indicating molecular restructuring during dissociation. The high kinetic energy C3H5 signals are assigned to allyl radicals generated by a minor photochemical pathway which involves concerted C-Br bond dissociation and cyclopropyl ring-opening following single UV-photon absorption. Slow photofragments also contribute to the velocity map images obtained at the C3H5 radical mass, but corresponding slow Br atoms are not observed. These features in the images are attributed to C3H5+ from the photodissociation of the C3H5Br+ molecular cation following two-photon ionization of the parent compound. This assignment is confirmed by 118-nm vacuum ultraviolet ionization studies that prepare the molecular cation in its ground electronic state prior to UV photodissociation.